Application and development of hydrogel biomaterials for the treatment of intervertebral disc degeneration: a literature review - Liu, Yuheng; Zhao, Zhen; Guo, Chuan; Huang, Zhangheng; Zhang, Weifei; Ma, Fei; Wang, Zhe; Kong, Qingquan; Wang, Yu (Frontiers in Cell and Developmental Biology, 2023)
Low back pain caused by disc herniation and spinal stenosis imposes an enormous medical burden on society due to its high prevalence and refractory nature. This is mainly due to the long-term inflammation and degradation of the extracellular matrix in the process of intervertebral disc degeneration (IVDD), which manifests as loss of water in the nucleus pulposus (NP) and the formation of fibrous disc fissures. Biomaterial repair strategies involving hydrogels play an important role in the treatment of intervertebral disc degeneration. Excellent biocompatibility, tunable mechanical properties, easy modification, injectability, and the ability to encapsulate drugs, cells, genes, etc. make hydrogels good candidates as scaffolds and cell/drug carriers for treating NP degeneration and other aspects of IVDD. This review first briefly describes the anatomy, pathology, and current treatments of IVDD, and then introduces different types of hydrogels and addresses “smart hydrogels”. Finally, we discuss the feasibility and prospects of using hydrogels to treat IVDD.